Identifikasi Sesar dengan Menggunakan Metode Gaya Berat (Studi Kasus: Sulawesi Tengah) - Mutia, Rara; Mardani, Mardani; Fathia, Suci; Kusmita, Tri (Jurnal Riset Fisika Indonesia, 2023)
The study of the geological structure of Sulawesi Island, especially the Central Sulawesi region, is very interesting because it has high complexity as a result of the dynamic interactions of the world's three main plates. Indications of high seismic activity and deformation processes in the Central Sulawesi region can be found from the morphological appearance and activity of several existing faults such as the Palu-Koro fault, the Lawanopo fault, and the Matano fault. The data used in this study are secondary data measuring the distribution of gravitational field anomalies (FAA) and topographical data using the Topex application. At CBA values ranging from 31 mGal to 56 mGal. The height anomaly on the CBA contour map is shown in red to light purple which has a value range of 40.7 mGal to 62.7mGal. Low anomaly is shown in light green to blue which has a value range of 27.3 mGal to 3.2 mGal. The regional gravity anomaly values range from 5.1 mGal to 62.8 mGal with a distribution of gravity anomalies from south to north. While in this study it can only be explained that the residual anomaly value is influenced by rock type and density. The high anomaly found in the southern part is thought to be caused by rocks having high density and being in a sedimentary rock environment which has low density.